1999
DOI: 10.1016/s0014-5793(99)00254-9
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 interacts with MDMX through their RING finger domains

Abstract: The N-terminus of MDM2 proto-oncoprotein interacts with p53 and down modulates p53 activity by inhibiting transcriptional activity and promoting p53 degradation. MDMX is structurally related to MDM2 and also binds to p53. However, the function of MDMX has not been clarified yet. We found that MDM2 hetero-oligomerized with MDMX through their Cterminal RING finger domains. Yeast two-hybrid analysis revealed that the hetero-oligomerization between MDMX and MDM2 was more stable than the homo-oligomerization of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
301
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(317 citation statements)
references
References 26 publications
15
301
0
1
Order By: Relevance
“…RBDs reported appear to be speci®c to certain RINGs where RINGs from other proteins are unable to interact. Alternatively, certain RING proteins bind selected RING proteins through their respective RINGs (Tanimura et al, 1999;Meza et al, 1999). Outside of RING RING interactions, the proline-rich region of PRH is the ®rst RBD that recognizes more than one RING.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RBDs reported appear to be speci®c to certain RINGs where RINGs from other proteins are unable to interact. Alternatively, certain RING proteins bind selected RING proteins through their respective RINGs (Tanimura et al, 1999;Meza et al, 1999). Outside of RING RING interactions, the proline-rich region of PRH is the ®rst RBD that recognizes more than one RING.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports show that RING proteins can bind other RING proteins through this domain (e.g. Tanimura et al, 1999;Meza et al, 1999). Others report that the RING can bind ubiquitin like molecules and ubiquitin hydrolase molecules (Jensen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The novel function does not appear to be binding to RNA (Elenbaas et al, 1996), since mutants with di erent e ects on cell cycle bind RNA with similar a nity (poly-G agarose beads, data not shown). The MDM2 RING ®nger has been reported to bind to TAF II 250 (Leveillard and Wasylyk, 1997) and MDMX (Sharp et al, 1999;Tanimura et al, 1999). It may also interact with speci®c E2s, in analogy with a number of RING ®nger proteins that have recently been shown to have E3 ubiquitin ligase activity and to bind to E2 ubiquitin conjugating enzymes (Hu and Fearon, 1999;Joazeiro et al, 1999;Lorick et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Mdm2 and MdmX hetero-oligomerize through their C-terminal RING finger domains (Tanimura et al, 1999). To determine whether Mdm2 competes for binding of USP2a to MdmX, a GST pull down assay was carried out.…”
Section: Usp2a Forms a Complex With Mdmxmentioning
confidence: 99%
“…It has also been suggested that MdmX may regulate the stability of p53 indirectly. Mdm2 and MdmX interact through their RING fingers and this interaction can stabilize Mdm2 and promote Mdm2-mediated degradation of p53 (Tanimura et al, 1999;Gu et al, 2002). However, in mice MdmX knockout increases p53 transcriptional activity but has little or no effect on p53 levels (Marine et al, 2006).…”
Section: Introductionmentioning
confidence: 99%